2019
DOI: 10.48550/arxiv.1912.00769
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phase behavior of a cell fluid model with modified morse potential

Abstract: The present manuscript gives a theoretical description of the first-order phase transition in a cell fluid model with a modified Morse potential and additional repulsive interaction. In the framework of the grand canonical ensemble, the equation of state of the system in terms of chemical potential-temperature and terms of densitytemperature is calculated for a wide range of density and temperature. The behaviour of the chemical potential as a function of temperature and density is investigated. The maximum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Recently in [25], we have shown that the zero-mode approximation describes well the phase behavior of a one-component fluid. It is a mean-field type approximation taking into account the contribution from the variable ρ k at k = 0.…”
Section: The Zero-mode Approximationmentioning
confidence: 96%
See 4 more Smart Citations
“…Recently in [25], we have shown that the zero-mode approximation describes well the phase behavior of a one-component fluid. It is a mean-field type approximation taking into account the contribution from the variable ρ k at k = 0.…”
Section: The Zero-mode Approximationmentioning
confidence: 96%
“…This move provides calculating the grand partition function of the model within a single approach of the collective variables method. This work summarizes the results of [25] in the case of an asymmetric binary system. We have found that the critical temperature of the mixture is a function of its composition, described a method for calculating the equation of state of the mixture, and shown its pressure behavior along the Widom line.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations